2014
DOI: 10.1093/cid/ciu866
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Virulence Genotype and Resistance Profile in the Mortality of Pseudomonas aeruginosa Bloodstream Infections

Abstract: Our results indicate that the exoU genotype, which is associated with specific susceptibility profiles, is a relevant independent marker of early mortality in P. aeruginosa bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
174
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(206 citation statements)
references
References 38 publications
16
174
8
2
Order By: Relevance
“…In addition, previous studies were shown that the presence of the TTSS effector genotypes, especially exoU genotype, correlate with increasing the virulence and resistance to one or more antibiotics. In a study by Agnello et al, they were found that the presence of exoU gene was significantly correlated with flouroquinolones-resistance (4 (23,26). In present study 81.7% and 88.6% of isolates were resistant to ciprofloxacin and levofloxacin; respectively.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, previous studies were shown that the presence of the TTSS effector genotypes, especially exoU genotype, correlate with increasing the virulence and resistance to one or more antibiotics. In a study by Agnello et al, they were found that the presence of exoU gene was significantly correlated with flouroquinolones-resistance (4 (23,26). In present study 81.7% and 88.6% of isolates were resistant to ciprofloxacin and levofloxacin; respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Fourteen P. aeruginosa ST175 isolates recovered from patients with bloodstream infections in a 2008 -2009 multicenter study in Spain were studied (18,22). The isolates selected included as many as 2 ST175 representatives for each of the 10 hospitals participating in the multicenter study.…”
Section: Methodsmentioning
confidence: 99%
“…The present data, together with the results obtained previously with INP1855 (35), strongly suggest an advantage for hydroxyquinolines over salicylidene acylhydrazides. Hydroxyquinolines, indeed, show better effects on both iT3SS and the fT3SS, two key determinants in the pathogenicity of P. aeruginosa (3,11,12,27,55).…”
Section: Discussionmentioning
confidence: 91%
“…ncreasing resistance of clinical isolates of Pseudomonas aeruginosa to current recommended antipseudomonal antibiotics is associated with poor clinical outcome and increased mortality (1)(2)(3), prompting the search for innovative therapeutic strategies. However, very few novel antipseudomonal agents are currently under development (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation